Utilizing Mathenge (Prosopis Juliflora) for Charcoal: The Other Side of an Invasive Species - Koech, G.; Wanjira, E.O.; Kirimi, M.; Siko, I.; Sola, P.; Bourne, M.; Muriuki, J.; Njenga, M. (2020)
The study used Focused Group Discussions (FGD), seasonal and livelihood calendars, participatory visioning and mapping and training of trainers delivered in partnership with KEFRI. Analysis from the project has showed that the species has potential to provide communities with 14 different products and services with charcoal ranking highest and food for humans the lowest. In terms of contribution to livelihoods, both men and women rank charcoal among the top three livelihood sources after farming and livestock keeping. Pods, another product from Prosopis can be sold as feed for livestock at KES 100 (USD1) per 50kg bag. Management by utilization of the almost 19,000 hectares of Prosopis juliflora in Baringo for sustainable charcoal production presents potential for improving livelihoods and the environment. It presents an opportunity for supplying the growing urban centers with affordable cooking fuel, a strategy that can be scaled out to the other affected counties. Also, there is need for complete removal of mathenge in some pockets to create room for enrichment with native high value multipurpose tree species to enhance biodiversity.